2012
DOI: 10.1016/j.celrep.2012.10.009
|View full text |Cite
|
Sign up to set email alerts
|

T cell Activation Is Driven by an ADP-Dependent Glucokinase Linking Enhanced Glycolysis with Mitochondrial Reactive Oxygen Species Generation

Abstract: Mitochondria-originating reactive oxygen species (ROS) control T cell receptor (TCR)-induced gene expression. Here, we show that TCR-triggered activation of ADP-dependent glucokinase (ADPGK), an alternative, glycolytic enzyme typical for Archaea, mediates generation of the oxidative signal. We also show that ADPGK is localized in the endoplasmic reticulum and suggest that its active site protrudes toward the cytosol. The ADPGK-driven increase in glycolytic metabolism coincides with TCR-induced glucose uptake, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
187
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 170 publications
(196 citation statements)
references
References 66 publications
9
187
0
Order By: Relevance
“…We and others have shown that rotenone, an inhibitor of complex I, blocks T-cell activation-induced ROS generation (Kaminski et al 2007;2010, 2012bYi et al 2006) and, consequently, IL-2, IL-4 and CD95L gene expression (Bauer et al 1998;Kaminski et al 2007Kaminski et al , 2010. Since rotenone interferes with centrosomal function and tubulin assembly (Brinkley et al 1974;Diaz-Corrales et al 2005;Marshall and Himes 1978;Ren et al 2005;), specificity of observed effects was confirmed by additional complex I inhibitors, piericidin A and metformin (an anti-diabetic and mild complex I blocker) (El-Mir et al 2000;Horgan et al 1968;Owen et al 2000).…”
Section: The Enzymatic Sources Of the Oxidative Signalmentioning
confidence: 99%
See 2 more Smart Citations
“…We and others have shown that rotenone, an inhibitor of complex I, blocks T-cell activation-induced ROS generation (Kaminski et al 2007;2010, 2012bYi et al 2006) and, consequently, IL-2, IL-4 and CD95L gene expression (Bauer et al 1998;Kaminski et al 2007Kaminski et al , 2010. Since rotenone interferes with centrosomal function and tubulin assembly (Brinkley et al 1974;Diaz-Corrales et al 2005;Marshall and Himes 1978;Ren et al 2005;), specificity of observed effects was confirmed by additional complex I inhibitors, piericidin A and metformin (an anti-diabetic and mild complex I blocker) (El-Mir et al 2000;Horgan et al 1968;Owen et al 2000).…”
Section: The Enzymatic Sources Of the Oxidative Signalmentioning
confidence: 99%
“…Thus, intact, functional respiratory complex I is indispensible for the oxidative signal generation. Importantly, PMA(DAG)-induced oxidative signal followed the TCR-induced one regarding responsiveness towards mtDNA depletion, all respiratory chain inhibitors tested and NDUFAF1 knock-down (Kaminski et al 2007(Kaminski et al , 2010(Kaminski et al , 2012b.…”
Section: The Enzymatic Sources Of the Oxidative Signalmentioning
confidence: 99%
See 1 more Smart Citation
“…Mitochondrial superoxide was also shown to regulate mitochondrial glycerol-3-phosphate dehydrogenase in T-cells. This metabolic shift results in increased glycolysis and increased reduction of mitochondrial respiratory chain (7). Described metabolic changes facilitate T-cell proliferation and cytokine production in models of other disease conditions; however, specific role of mitochondrial superoxide in the immune cells-mediated hypertension is not defined.…”
Section: R99 Mitochondrial Ros In the Prohypertensive Immune Responsementioning
confidence: 99%
“…Oxidative signals can be regulated by the TCRtriggered activation of ADP-dependent glucokinase (ADPGK), which increases glycolytic metabolism and diverts glycolysis toward the mitochondrial glycerol-3-phosphate dehydrogenase (GPD) shuttle. The activation of GPD2 results in hyperreduction of ubiquinone and release of ROS from mitochondria, resulting in the upregulation of NF-κB-dependent gene expression [93]. Mitochondrial ROS signaling is thus required for antigen-specific T cell activation, highlighting the critical importance of mitochondrial metabolism in the regulation of the T cell nuclear program.…”
Section: Mitochondria Ros and Nuclear Activationmentioning
confidence: 99%